Immunocytochemical characterization of ex vivo cultured conjunctival explants; marker validation for the identification of squamous epithelial cells and goblet cells - Van Acker, Sara I.; Van den Bogerd, Bert; Haagdorens, Michel; Koppen, Carina; Pintelon, Isabel (Frontiers in Medicine, 2023)
Tissue-engineered products are at the cutting edge of innovation considering their potential to functionally and structurally repair various tissue defects when the body’s own regenerative capacity is exhausted. At the ocular surface, the wound healing response to extensive conjunctival damage results in tissue repair with structural alterations or permanent scar formation rather than regeneration of the physiological conjunctiva. Conjunctival tissue engineering therefore represents a promising therapeutic option to reconstruct the ocular surface in severe cicatrizing pathologies. During the rapid race to be a pioneer, it seems that one of the fundamental steps of tissue engineering has been neglected; a proper cellular characterization of the tissue-engineered equivalents, both morphologically and functionally. Currently, no consensus has been reached on an identification strategy and/or markers for the characterization of cultured squamous epithelial and goblet cells. This study therefore evaluated the accuracy of promising markers to identify differentiated conjunctival-derived cells in human primary explant cultures through immunocytochemistry, including keratins (i.e., K7, K13, and K19) and mucins (i.e., MUC1, MUC5AC, and PAS-positivity). Comparison of the in vivo and in vitro cellular profiles revealed that the widely used goblet cell marker K7 does not function adequately in an in vitro setting. The other investigated markers offer a powerful tool to distinguish cultured squamous epithelial cells (i.e., MUC1 and K13), goblet cells (i.e., MUC5AC and PAS-staining), and conjunctival-derived cells in general (i.e., K19). In conclusion, this study emphasizes the power alongside potential pitfalls of conjunctival markers to assess the clinical safety and efficacy of conjunctival tissue-engineered products.